SAT0350 A ROLE FOR IL-17A IN THE SUPPRESSION OF SPINAL ENTHESEAL MESENCHYMAL STEM CELL ADIPOGENESIS WHILST SIMULTANEOUSLY FACILITATING OSTEOGENESIS. (2nd June 2020) - Russell, T.; Bridgewood, C.; Khan, A.; Rao, A. S.; Loughenbury, P.; Millner, P.; Dunsmuir, R.; Altaie, A.; Jones, E.; Mcgonagle, D.
Abstract : Background: Fat formation in the bone adjacent to the enthesis is an important but poorly characterised intermediate stage in new bone formation that occurs in the spine in AS. We and others have previously reported that IL-17A can increase mesenchymal stem cell (MSC) mediated osteogenesis in normal and AS spinal tissue (1, 2). Objectives: Herein we investigate the impact of IL-17A & TNF on MSC adipogenesis from spinal enthesis tissue. Methods: Samples from healthy spinous process and interspinous ligament (n=14, median age = 53) were separated into the peri-entheseal bone (PEB) and entheseal soft tissue (EST) & enzymatically digested. Minimally passaged (<p3) MSCs were cultured in a complete adipogenic media, with some cultures supplemented with either IL-17A (50ng/ml), TNF (1ng/ml) or IL-17A & TNF for 3 weeks. Adipogeneis was quantitatively assessed by Oil Red O staining at day 21. IL-17A's effect on adipogeneis was further investigated by RNA extractions at Day 0, 3, 5, 7, 15 & 21 with supporting Oil Red O staining. 48 adipogenic and IL-17A target genes were used to investigate adipogenic progression and IL-17A effects on it over 21 day adipogenic differentiation. Results: EST MSCs have a significantly higher adipogenic potential than matched PEB MSCs (n=14, p<0.001). TNF and IL-17A both cause significant decreases (all p<0.01, n=5) in adipogenesis for both PEB and EST MSCs. EST MSCs produced lipid vesicles by day-3 post-induction, with significant inhibition by IL-17A (p<0.01, n=4) seen from day 15 onwards. IL-17A caused a significant decrease in overall Oil Red O staining, and it changed the morphology of lipid vesicles with a majority of cells consistent with immature pre-adipocytes. This was supported by gene expression data, which indicated significant decreases in transcripts encoding vesicle fusion proteins (CIDEC p<0.05, PLIN1 p<0.01). PLIN1 also aids protection against lipolysis (4). Transcripts associated with osteogenesis (CEBPβ (3)) and MSC stromal support (CXCL12) were significantly upregulated in adipogenically-induced cultures stimulated with IL-17A when compared to control adipogenic media. TNF & IL-17A combination demonstrated that IL-17A drove the vesicle morphology changes, with TNF alone not showing the same vesicle changes. Conclusion: Given the inverse link between MSC mediated osteogeneis & adipogenesis, these findings reveal a role of IL-17A especially on EST MSCs. The rapid formation of adipocytes seen in EST MSCs may be relevant to MRI determined peri-entheseal bone "shiny corners" due to post inflammation fat accumulation. Elevated transcripts associated with pre-adipocytes & undifferentiated MSCs support the idea of plasticity between early osteogenesis & adipogenesis. Downregulation of transcripts for proteins associated with protection against lipolysis allows for the rationalising of the gradual loss of the shiny corners seen in AS preceding subsequent new bone formation. References: [1]RUSSELL, T., A. WATAD, C. BRIDGEWOOD, A. KHAN, A.S. RAO, P. LOUGHENBURY, P. MILNER, R. DUNSMUIR, T. BABOOLAL, E. JONES, R. CUTHBERT and D. MCGONAGLE. IL-17A Induces Distinct Functional Differences Between Two Novel Mesenchymal Stem Cell Populations Identified at the Human Enthesis. Arthritis Rheumatol, 2019, 71 Suppl 10, pp.1-5362. [2]JO, S., S.E. WANG, Y.L. LEE, S. KANG, B. LEE, J. HAN, I.H. SUNG, Y.S. PARK, S.C. BAE and T.H. KIM. IL-17A induces osteoblast differentiation by activating JAK2/STAT3 in ankylosing spondylitis. Arthritis Res Ther, 2018, 20(1), p.115. [3]AHMED, M. and S.L. GAFFEN. IL-17 in obesity and adipogenesis. Cytokine Growth Factor Rev, 2010, 21(6), pp.449-53. [4]HANSEN, J.S., S. DE MARE, H.A. JONES, O. GORANSSON and K. LINDKVIST-PETERSSON. Visualization of lipid directed dynamics of perilipin 1 in human primary adipocytes. Sci Rep, 2017, 7(1), p.15011. Disclosure of Interests: Tobias Russell Grant/research support from: Novartis UK Investigator Initiated non-clinical research funding support, Charlie Bridgewood: None declared, Almas Khan: None declared, Abhay S Rao: None declared, Peter Loughenbury: None declared, Peter Millner: None declared, Robert Dunsmuir: None declared, Ala Altaie: None declared, Elena Jones: None declared, Dennis McGonagle Grant/research support from: Janssen Research & Development, LLC